Voices of the Marginalized: Examining Palestine's Quest for Justice through the Lenses of Sen, Rawls, and Said - Nazrul, Nelufer (MID Publisher International, 2024)
This article explores Amartya Sen's 'capacity approach', John Rawls 'theory of justice' and Edward Said's critique of 'Orientalism' to analyse the quest for justice in Palestine. This article provides an extensive analysis of the challenges faced by Palestinians and proposes potential solutions to address these issues. Sen's capability approach centers on the various forms of deprivation experienced by Palestinians living under occupation, such as restricted mobility, limited access to resources, and constrained economic opportunities. Following Rawls' theory of justice, this paper examines violations of human rights, the principles of self-government, and distribution of resources. While stressing the analysis of the Palestinian case we will pay most attention to the continuous violation of freedom and fairness. Said has critiqued Orientalism making people aware of ignoring the hegemonic discourses that erased the Palestinians, stressing the importance of speaking for oneself. The focus of the essay is the Palestinian resistance as a complex process, which is described by the human development, justice, rights, and representation. These are tangible policies that aim at the complete banning of movement restrictions, ending systemic discrimination in resource allocation, protection of Palestinians' rights, encouragement of free speech, and accord more power to Palestinian stakeholders in the decision making organs. In order for Palestinians to achieve justice and self-determination, the article argues that a comprehensive strategy is required that addresses injustice, upholds fundamental human rights and dignity, and amplifies the voices of marginalized individuals.